In vitro trypanocidal activity of solamargine and extracts from Solanum palinacanthum and Solanum lycocarpum of brazilian cerrado - Moreira, Raquel Regina Duarte [UNESP]; Martins, Gilmarcio Z.; Magalhaes, Nathalia O.; Almeida, Adelia Emilia de [UNESP]; Pietro, Rosemeire C. L. R.; Silva, Flavia A. J.; Cicarelli, Regina Maria Barretto [UNESP] (Academia Brasileira de Ciências, 2013)
O objetivo deste estudo foi avaliar a potencial atividade tripanocida do extrato bruto etanólico dos frutos de Solanum palinacanthum, Solanum lycocarpum e do glicoalcalóide solamargina. Pó do fruto seco de S. palinacanthum e S. lycocarpum foram submetidos a extracção por refluxo com etanol a 96% e solamargina foi isolada a partir do extrato bruto de S. palinacanthum. Foram determinadas de ambos os extratos e a solamargina a atividade tripanocida utilizando o ensaio colorimétrico MTT. O Extrato de S. palinacanthum mostrou-se mais ativo (IC50 = 175,9 µg.ml–1) de que o extrato de S. lycocarpum (IC50 = 194,7 µg.ml–1). A solamargina apresentou forte atividade tripanocida (IC50 = 15,3 µg.ml–1), o que pode explicar a melhor atividade de ambos os extratos. O benzonidazol (IC50 = 9,0 µg.ml–1) é a única droga utilizada para o tratamento da doença de Chagas. Estes resultados demonstram pela primeira vez que os extratos etanólicos obtidos a partir de frutos de S. palinacanthum e S. lycocarpum, além da solamargina apresentam uma atividade tripanocida potencial.

The present investigation was to evaluate the potential trypanocidal activity of crude ethanolic extract of the fruits of Solanum palinacanthum, Solanum lycocarpum and the glycoalcaloid, solamargine. S. palinacanthum and S. lycocarpum fruit powders were submitted to exhaustively extraction with 96% ethanol and solamargine were isolated from the extract of S. palinacanthum. Both extracts and solamargine were analysed for trypanocidal activity by using MTT colorimetric assay. Extracts of S. palinacanthum showed to be more active (IC50 = 175.9 µg.ml–1) than S. lycocarpum (IC50 = 194.7 µg.ml–1). Solamargine presented a strong activity (IC50 = 15.3 µg.ml–1), which can explain the better activity of the both extracts. Benznidazol (IC50 = 9.0 µg.ml–1) is the only drug used to treat Chagas' disease. These findings demonstrate for the first time that ethanol extracts obtained from both fruits of S. palinacanthum and S. lycocarpum and also solamargine have a potential anti-trypanosomal activity.
Keywords: Solanum palinacanthum; Solanum lycocarpum; solamargina; epimastigota; atividade tripanocida; Trypanosoma cruzi; Solanum palinacanthum; Solanum lycocarpum; solamargine; epimastigote; antitrypanosomal activity; Trypanosoma cruzi